The historical narrative of Jose Carlos Mariategui: The construction of a revolutionary subjectivity in the Peruvian Andes - Nación Pantigoso, Miguel Ángel (2018)
Between the end of the nineteenth century and first decades of twentieth century, the Peruvian intelligentsia discussed what State the Peruvian society required. The question was faced with the help of the modern social sciences like sociology and scientific history. However, the building of Nation-State required a view of the society like totality. This means a history about the past, the present and future. José Carlos Mariátegui made a modern narrative about the Peruvian Nation-State disagreeing with consolidated narrative, i.e. positivist narrative and spiritualist narrative. Mariátegui’s narrative was articulated by two principles or central concepts: myth and indio. These concepts together with a Marxist framework built the modern narrative of Peruvian society and the revolutionary subject of Peruvian history.